2011
DOI: 10.4103/0974-2700.82224
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal compartment syndrome - Intra-abdominal hypertension: Defining, diagnosing, and managing

Abstract: Abdominal compartment syndrome (ACS) and intra-abdominal hypertension (IAH) are increasingly recognized as potential complications in intensive care unit (ICU) patients. ACS and IAH affect all body systems, most notably the cardiac, respiratory, renal, and neurologic systems. ACS/IAH affects blood flow to various organs and plays a significant role in the prognosis of the patients. Recognition of ACS/IAH, its risk factors and clinical signs can reduce the morbidity and mortality associated. Moreover, knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 114 publications
0
95
0
6
Order By: Relevance
“…First, elevated abdominal pressure affects the cardiovascular system by increasing intrathoracic pressure [13], which in caused by reduced hepatic blood flow, and abdominal wall ischemia [11,14]. As shown in Table 1 Table 2 indicated that partial pressure of carbon dioxide was elevated to 42 mmHg, while partial pressure of oxygen had fallen to 121 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, elevated abdominal pressure affects the cardiovascular system by increasing intrathoracic pressure [13], which in caused by reduced hepatic blood flow, and abdominal wall ischemia [11,14]. As shown in Table 1 Table 2 indicated that partial pressure of carbon dioxide was elevated to 42 mmHg, while partial pressure of oxygen had fallen to 121 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, there were no signs of aspiration before or after induction, the bilateral airway entry was auscultated, and neither the tidal volume nor inspiratory gas flow rate were manipulated until PIP increased. In addition, we checked that the breathing circuit was not bent, and confirmed the tube location once again, A perioperative increase of abdominal pressure may have various causes, including hemorrhage, edema, ileus, and abscess [11,12]. Elevated abdominal pressure not only disturbs the local blood flow within the abdominal cavity but also has detrimental effects on non-abdominal organs and systems.…”
Section: Discussionmentioning
confidence: 99%
“…13 Thus it is advisable every time the closure of the abdominal wall is not possible or determines a high risk of complication with need of relaparotomy. 18 With this kind of operation, revisions allow to identify quickly anastomotic dehiscences or any problem that can occur into the abdomen. 19 Caronna et al hypothesised the usefulness of laparostomy for the early diagnosis and treatment of complications in management of typhoid intestinal perforation in rural hospital in northwestern Benin.…”
Section: Discussionmentioning
confidence: 99%
“…These set of findings represent the abdominal compartment syndrome caused by massive retroperitoneal and interstitial swelling. 4 In 2004, the World Society of Abdominal Compartment Syndrome (WSACS) was established by an international group of surgeons and physicians. They recognized the need for a cohesive approach fostering education, promoting research, treating and improving the survival of patients suffering from IAH and ACS.…”
Section: Discussionmentioning
confidence: 99%